EVALUATION STRATEGIES AND APPROACHES IN LEARNING ISLAMIC RELIGIOUS EDUCATION: AN ANALYSIS BASED ON THE ISLAMIC EDUCATION EVALUATION DEVELOPMENT BOOK - Pahlevi, Muhammad Syahreza; Hafidz, Hafidz (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
Evaluation of Islamic Religious Education (PAI) learning is an important element in measuring the success of the educational process that includes cognitive, affective, and psychomotor aspects. However, its implementation is faced with various challenges, such as limited evaluation methods, instrument development, and teacher competence in carrying out holistic evaluations. This study aims to examine the concept, challenges, and strategies for developing PAI evaluation through a literature study approach with descriptive analysis of various library sources. The results of the study indicate that the main challenge in PAI evaluation is the dominance of conventional methods that are less able to capture the affective and psychomotor aspects of students optimally. The proposed strategies include the development of varied instruments, teacher training, technology integration, and collaboration with parents. The implications of this study are the need for improvements to education policies to support the implementation of more effective PAI evaluations that are oriented towards the formation of student character according to Islamic values.